Synthesis and Theoretical Study of new N-(3-methyl 5-isothiazolyl) maleimide derivativs (Latakia University Journal -Basic Sciences Series, 2019)
New derivative N-(3-methyl, 5-isothiazolyl) maleimide have been Synthesized via Diels- Alder Reaction between maleimide with each of furan and 2,3-di methyl butadiene.The structure of synthesized compound have been established on the basic of their spectral (IR, 1HNMR, elemental analysis) data. Maleimide was treated with furan to give two isomers were (endo),(exo).The proportion of each isomer has been different dependence reaction temperature.The thermodynamic properties of reaction have been determined using the theoretical Methods CBS-4m, B3PW91,  MPW1PBE and MPW1PW91.The all theoretical methods  results have been accorded with the experimental method results .